Patient Attitudes toward Gestational Weight Gain and Exercise during Pregnancy - M. L. Lott; M. L. Power; E. G. Reed; J. Schulkin; A. D. Mackeen (Hindawi Limited, 2019)
Body mass index (BMI) and gestational weight gain (GWG) are important factors for neonatal and maternal health. Exercise helps women moderate their BMI and GWG, and provides health benefits to mother and child. This survey study assessed patients' perceptions of counseling they received during pregnancy, their sources of information about GWG, and their attitudes toward exercise during pregnancy. We distributed an anonymous survey to 200 pregnant women over the age of 18 at a tertiary care center in Danville, Pennsylvania. Survey questions included demographics, discussions with medical providers regarding GWG and exercise, and their exercise habits before and during pregnancy. 182 women (91%) responded. Most reported their provider discussed weight and diet (78.8%), expected GWG (81.6%), and exercise during pregnancy (79.8%); however, 28% of obese women and 25% of women who did not plan to exercise during pregnancy reported not receiving exercise counseling. Approximately 20% of women did not plan to exercise during pregnancy. Women decreased the number of days per week they exercised (40.6% with 3 or more days prepregnancy versus 30.7% during pregnancy, P=0.002). Some patients who did not exercise prior to pregnancy (12%) expressed interest in a personal training session. Among women in the eight month or later, 42.4% were above GWG recommendations. Our study found barriers to adequate activity during pregnancy; 20% of pregnant women not receiving/remembering counseling regarding exercise. Interest in personal training from patients that did not exercise suggests they would benefit from increased efforts to encourage physical activity. Exercise and GWG counseling based in medical science as well as patient psychological needs will help efforts to reduce GWG and improve pregnancy outcomes.